Accelerometer‐measured physical activity, sedentary behavior, and sleep in children with cerebral palsy and their adherence to the 24‐hour activity guidelines. (14th July 2022) - Hulst, Raquel Y.; Gorter, Jan Willem; Obeid, Joyce; Voorman, Jeanine M.; van Rijssen, Ilse M.; Gerritsen, Anke; Visser‐Meily, Johanna M. A.; Pillen, Sigrid; Verschuren, Olaf
Abstract: Aim: To measure and describe the 24‐hour activities (i.e. physical activity, sedentary behavior, and sleep) and to examine adherence to the 24‐hour activity guidelines among children with cerebral palsy (CP) using actigraphy. Method: Children's 24‐hour activities were recorded over 7 days using hip‐ and wrist‐worn ActiGraph wGT3X‐BT accelerometers. Results: In total, 362 days and 340 nights from 54 children with CP (Gross Motor Function Classification System [GMFCS] levels I–III; 44% females; median age [range] 6 years 6 months [3–12 years]) were included. Mean (SD) daily wear time was 746.2 (48.9) minutes, of which children spent on average 33.8% in light physical activity (251.6 [58.7] minutes per day), 5.2% in moderate‐to‐vigorous physical activity (38.5 [20.1] minutes per day), and the remaining 61.1% being sedentary (456.1 [80.4] minutes per day). Physical activity decreased while sedentary behavior increased with increasing GMFCS level. In total, 13% of all children met the physical activity recommendations, and 35% met the age‐appropriate sleep duration recommendation. The proportion of children meeting the combined 24‐hour guidelines for physical activity and sleep was low (5.9%), especially in those classified in GMFCS level III (0%). Interpretation: The observed low 24‐hour guideline adherence rates emphasize the importance of considering the entire continuum of movement behaviors in the care of children with CP, in efforts to promote healthy lifestyle behaviors and prevent negative health outcomes. Abstract : Visual abstract of the adherence to the 24‐hour activity guidelines.